ISOTOPE FRACTIONATION RELATED TO KIMBERLITE MAGMATISM AND DIAMOND FORMATION - Galimov E.M. (My University, 1991)
This paper deals with a model of carbon isotope fractionation presumed to accompany the movement of mantle fluids. In the first part of the article, the experimental data and the relationships revealed are generalized and discussed; the remainder of the paper describes the model. The isotope compositions of different forms of carbon related to kimberlite magmatism vary widely. In diamonds, δ13C values range from −34.5 to +2.8%.. Carbonate-bearing autholiths in kimberlites occur enriched in 13C up to +35 %.. Organic matter, including that occurring in fluid inclusions of magmatic minerals of kimberlites, is depleted in 13C down to − 30%.. It is concluded that the δ13C-distribution for diamonds is specific for a particular occurrence (different kimberlite pipes, different regions, etc.). Principal differences in isotopic distribution patterns for diamonds of ultrabasic and basic paragenesis exist. Isotopically light diamonds are related only to the latter. When a diamond consists of several sequential generations of growth (coated diamonds, diamond-in-diamond), δ13C values of the early generation vary widely, whereas the isotopic composition of the latter is more uniform.